Grafos, avaliação e o sistema educacional brasileiro - Leite, Luiz Augusto de Almeida Mascarenhas (2022)
The systemic evaluation of public networks is a mechanism for social and democratic control of the quality of education offered by public schools. The general objective of this work is to create a model based on graph theory that relates schools and students' proficiency in large-scale assessment. For this, the database of the Pernambuco State Assessment System (SAEPE) was used, from 2010 to 2019. This model uses schools as vertices of a graph and edges weighted as the proficiency of students. students. And the relationship between the vertices happens as students complete their educational cycles and change educational institutions. This movement of students was initially observed with data from 2010 in the initial years of schooling. And it ends in 2019 with the end of the last cycle of basic education (third year of high school). In addition, we use Dijkstra's algorithm to find the best school trajectory a student should follow within a public education network. Finally, we performed this model computationally using data from a municipality in the State of Pernambuco. And we present the results obtained.